Trajectories of Depressive Symptoms Among North American Indigenous Adolescents: Considering Predictors and Outcomes. Issue 3 (31st July 2019) - Martinez, Miriam M.; Armenta, Brian E.
Abstract : We identified developmental trajectories of depressive symptoms among 674 Indigenous adolescents ( M age = 11.10, SD = 0.83 years) progressing from early to late adolescence. Four depressive symptoms trajectories were identified: (a) sustained low, (b) initially low but increasing, (c) initially high but decreasing, and (d) sustained high levels of depressive symptoms. Trajectory group membership varied as a function of gender, pubertal development, caregiver major depression, and perceived discrimination. Moreover, participants in the different trajectory groups were at differential risk for the development of an alcohol use disorder. These results highlight the benefit of examining the development of depressive symptoms and the unique ways that depressive symptoms develop among North American Indigenous youth as they progress through adolescence.